Big Data Improving Recommendation Quality in Music Applications - Yuzhong Zhang; Ai Fang; Duo Jin; Liyu Yuan (Dianxin kexue)
The process and methods of big data improved recommendation quality in music applications were focused. The individual music score system referring RFM model was described. The sparsity and overlapping and reliability was applied to adjust recommendation algorithm, combined soaring words and content labels and filtering rules with mixing recommendation to resolve the common problems of recommendation system.